Subtype and Regional-Specific Neuroinflammation in Sporadic Creutzfeldt–Jakob Disease - Llorens, Franc; López-González, Irene; Thüne, Katrin; Carmona, Margarita; Zafar, Saima; Andréoletti, Olivier; Zerr, Inga; Ferrer, Isidre (Frontiers in Aging Neuroscience, 2014)
The present study identifies deregulated cytokines and mediators of the immune response in the frontal cortex and cerebellum of sCJD MM1 and VV2 subtypes compared to age-matched controls. Deregulated genes include pro- and anti-inflammatory cytokines, toll-like receptors, colony stimulating factors, cathepsins, members of the complement system, and members of the integrin and CTL/CTLD family with particular regional and sCJD subtype patterns. Analysis of cytokines and mediators at protein level shows expression of selected molecules and receptors in neurons and/or in astrocytes and/or in microglia thus suggesting interactions between neurons and glial cells, mainly microglia, in the neuroinflammatory response in sCJD. Similar inflammatory responses have been shown in the tg340 sCJD MM1 mice, revealing a progressive deregulation of inflammatory mediators with disease progression. Yet inflammatory molecules involved are subjected to species differences in humans and mice. Moreover, inflammatory-related cell signalling pathways NFκB/IKK and JAK/STAT are activated in sCJD and sCJD MM1 mice. Together, the present observations show a self-sustained complex inflammatory and inflammatory-related responses occurring already at early clinical stages in animal model and dramatically progressing at advanced stages of sCJD. Considering this scenario, measures tailored to modulate (activate or inhibit) specific molecules could be therapeutic options in CJD.